Implementation of Responsibility Accounting (Case Study at PG. Kebon Agung) - Abdillah, Pujangga (Jurnal Ilmiah Mahasiswa FEB, 2016)
Development and competition in the business world requires companies to anticipate various possibilities that can affect them. Responsibility accounting is a system tailored to the characteristics and activities of the company with the aim of making each organizational unit responsible for the results of the activities under its supervision. This study aims to determine the practice and performance evaluation of responsibility accounting at PG. Kebon Agung. This research is classified as descriptive qualitative study. Case study is used as the method of the research, which is designed to answer the research question. The focus of the research is the organizational structure, budgeting, classification of costs, accounting systems, and the budget reporting system. This study examines issues related to the interpretation of responsibility accounting and its implementation in PG. Kebon Agung. The results of this concluded that the organizational structure and budgeting in Production Unit of PG. Kebon Agung were satisfying. Classification of costs and accounting system meet the requirements based on responsibility accounting. However, the budget reporting system did not include the existing management below. PG. Kebon Agung should involve all levels of management in its budget reporting system and make the procurement more transparent.Â Â  Key Words : Responsibility accounting, organization structure, implementation